REBOUND OBESITY AFTER GLP-1 AGONISTS DISCONTINUATION - Zainab M. Al-Shammaa; Heba M. Attash; Luma Al-Obaidy (Global Journal of Public Health Medicine)
Introduction: Discontinuation of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) often results in rebound obesity and excessive weight regain. This review explores the physiological, psychological, and behavioural factors contributing to weight regain after the discontinuation of GLP-1 RAs. Methods: This narrative review involved a review of literature published in PubMed, Scopus, Embase, Web of Science, and Google Scholar. The search for peer-reviewed literature in English started on 8 March 2025 and was repeated for updates on 25 March 2025. Results: The literature search identified only five studies that examined weight regain following the discontinuation of GLP-1 receptor agonists. These studies found that some users of these agents had regained the weight they lost before upon discontinuing GLP-1RAs. The proposed mechanism for this phenomenon is that abrupt cessation of appetite inhibition induced by GLP-1RAs leads to a surge in hunger, reduced energy expenditure, and fat mass gain. Psychological factors, like emotional overeating and dependence on the therapy, further exacerbate rebound. Clinical studies show significant weight regain after stopping semaglutide, liraglutide, or tirzepatide. Conclusion: This review focuses on the complex phenomenon of rebound obesity that may develop upon GLP-1 RAs discontinuation, emphasizing the need for comprehensive strategies to manage weight regain. Potential approaches include gradual dose reduction, combination therapies, and lifestyle interventions to mitigate weight regain.